Auditoría en seguridad vial, en la ruta nacional 25 del tramo Pr 86+000 al Pr 88+000 y ruta nacional 29 del tramo Pr 10+000 al Pr 11+000 del sector Cerritos – Pereira (2024)
The Road Safety Audit is a systematic and preventive process that seeks to identify and evaluate possible safety problems on the roads, with the aim of proposing solutions that mitigate risks and improve road safety.